Culprit lesion morphology in young patients with ST-segment elevated myocardial infarction: A clinical, angiographic and optical coherence tomography study. (October 2019) - Fang, Chao; Dai, Jiannan; Zhang, Shaotao; Wang, Yidan; Wang, Jifei; Li, Lulu; Wang, Yini; Yu, Huai; Wei, Guo; Zhang, Xiling; Feng, Na; Liu, Huimin; et al.
Abstract: Background and aims: About 20% of patients with ST-segment elevated myocardial infarction (STEMI) are young adults. Morphological characteristics of culprit lesion in young STEMI patients have not been systematically evaluated in vivo . The present study aimed to investigate culprit lesion characteristics in young patients versus older patients using optical coherence tomography (OCT). Methods: 1442 STEMI patients who underwent OCT examination of culprit lesion were included and divided into young group (age ≤50 years, n = 400) and older group (age >50 years, n = 1042). Clinical characteristics, angiography and OCT findings were compared between the two groups. Results: Culprit lesions in STEMI patients aged ≤50 years had more plaque erosion (32.0% vs. 21.1%, p  < 0.001) and larger minimal lumen area (2.3 ± 1.7 mm 2 vs. 1.9 ± 1.1 mm 2, p  < 0.001) than in those aged >50 years. As compared with older patients, lipid rich plaque (80.5% vs. 87.2%, p  = 0.001), thin cap fibroatheroma (TCFA, 59.5% vs. 69.5%, p  < 0.001), calcification (31.3% vs. 48.7%, p  < 0.001), spotty calcification (25.3% vs. 36.1%, p  < 0.001) and cholesterol crystals (26.3% vs. 38.4%, p  < 0.001) were less frequently observed in young patients. A gradient increase in typical plaque vulnerability was observed from age ≤50 years to 50–70 years to >70 years. In multivariate regression analysis, age ≤50 years was independently associated with less frequency of plaque rupture, TCFA, spotty calcification, cholesterol crystals and smaller lumen area stenosis. Conclusions: Morphological characteristics of culprit lesion in young STEMI patients were different from those in older patients. Patients aged ≤50 years had more plaque erosion and less vulnerable plaque features. Graphical abstract: Image 1 Highlights: Largest prospective optical coherence tomography study of STEMI in young patients. Mechanisms of STEMI in young and older patients were different. Age was an independent predictor of culprit lesion morphology in STEMI patients. Culprit lesions in patients aged ≤50 years have less vulnerable characteristics.